The impact of endometriosis upon quality of life: a qualitative analysis. - Jones, G; Jenkinson, C; Kennedy, S (2004)
OBJECTIVE: to explore and describe the impact of endometriosis upon quality of life. SETTING: Nuffield Department of Obstetrics and Gynaecology, University of Oxford. DESIGN: qualitative study. SAMPLE: twenty-four women with a laparoscopic diagnosis of endometriosis. METHODS: face to face, individual, in-depth interviews. RESULTS: analysis of the data revealed 15 descriptive categories. Pain, physical functioning, role performance, social functioning, emotional well-being, relationship with the medical profession, treatment, sexual intercourse, energy and vitality, employment and infertility were found to be a particular concern for women with endometriosis. Physical appearance, lack of control and powerlessness, feelings of social isolation and concerns that their daughters might develop endometriosis were new areas found to be negatively affected by the condition. CONCLUSIONS: the impact of endometriosis-associated symptoms upon quality of life is multidimensional and more complex than just negatively affecting psychosocial parameters. Conducting in-depth interviews to explore the subjective experiences of patients with endometriosis enabled the diverse areas of quality of life to be identified. Adopting a qualitative methodology is essential for item generation on disease specific health status questionnaires.